Existence of bovine neonatal pancytopenia before the year 2005? Retrospective evaluation of 215 cases of haemorrhagic diathesis in cattle. (October 2016) - Stoll, A.; Pfitzner-Friedrich, A.; Reichmann, F.; Rauschendorfer, J.; Roessler, A.; Rademacher, G.; Knubben-Schweizer, G.; Sauter-Louis, C.
Highlights: Results of the retrospective study show the occurrence and clinical findings of cases of haemorrhagic diathesis in cattle. Receiver operating characteristic curves were performed to provide predictive information of the outcomes of the diseases. Cases of bovine neonatal pancytopenia, which occurred before the associated vaccine was licensed, were investigated. Abstract: Haemorrhagic diathesis (HD) in cattle is a relatively rare syndrome that can have many different causes. With the occurrence of bovine neonatal pancytopenia (BNP) in 2007, the number of cases of HD in cattle has increased. This led to an enhanced interest in diseases presenting with bleeding disorders. The possible causes of HD in cattle, the clinical findings, and the course of various diseases are described and evaluated. Furthermore, we determined whether cases of BNP occurred before the introduction of the vaccine Pregsure BVD since its widespread use was associated with the syndrome. Records of 215 cases of HD in cattle that had been referred to the Clinic for Ruminants with Ambulatory and Herd Health Services at the Centre for Clinical Veterinary Medicine, Ludwig Maximilian University, Munich, between 1982 and 2014 were evaluated. The two most commonly diagnosed diseases were BNP ( n = 95) and septicaemia ( n = 35), with fatality rates of 82% and 66%, respectively. In 27 (13%) cases, no clear cause for the HD could be designated. Statistically significant differences were found with regard to the course of the various disorders and the clinical findings. A receiver operating characteristic analysis of thrombocyte counts of affected animals at the time of arrival at the clinic did not provide any predictive information on disease outcome. Two cases of HD occurred before the introduction of Pregsure BVD (1989, 1991). In both cases, clinical, haematological, and pathological findings were identical to BNP. The cause of HD in these two cases could not be determined retrospectively.